Persepsi pelajar terhadap pelaksanaan teknologi maklumat dan komunikasi dalam pengajaran dan pembelajaran - Noor Azahariah, Zainon (2008)
The purpose of this research is to study the students' perception towards the factors that influence the implementation of ICT in teaching and learning . The factors studied are the importance of the ICT, interest, attitude, teacher's personality and peer group influence. The research was done in order to determine the relationship between the factors involved. It aims to determine the differences in perception between students from the urban areas and the rural areas. It also aims to study the perceptions of students from the science and art streams. This research involves 240 respondents among the form four students of SMK Bandar Darulaman, SMK Jitra, SMK Changlun and SMK Tunku Bendahara. The Likert five points scale is used to get the students' response. The questions asked are based on the five factors studied. The data obtained is analysed using the descriptive statistical method to determine the frequency, percentage, mean and standard deviation. The inference statistical method which includes t-test and Pearson correlation are also used to analyse the data. The Pearson correlation test is used to study the correlation between the factors. The t-test is used to determine the differences in perception between gender, students from the urban and the rural areas, students from the Science and the Art streams as well as between students who own and do not own a computer. The finding shows that these five factors have a strong influence in the implementation of ICT in teaching and learning. The Pearson correlation test shows that there are significant correlations between the factors studied. The result of the t-test shows that there are no differences in perception between gender, students from the urban and the rural areas as well as students from art and science streams. However the t-test also shows that there are differences in perception between students who own a computer and students who do not own a computer